2020
DOI: 10.5114/aoms.2018.77036
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum polysaccharides exert an antioxidative effect on rat chondrocytes by activating the nuclear factor (erythroid-derived 2)-like 2 signaling pathway

Abstract: Introduction: Oxidative stress is the main cause of osteoarthritis (OA). Lycium barbarum polysaccharides (LBP) have antioxidant properties. Thus, the potential effect of LBP on H 2 O 2-stimulated chondrocytes was examined. Material and methods: The cell viability was detected by CCK-8. The reactive oxygen species (ROS) production and apoptosis rates were determined by flow cytometric analysis. The DNA damage was detected by comet assay. Real-time polymerase chain reaction (qPCR) and Western blot assays were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Cell experiments have demonstrated that NPs from herbs could regulate Nrf2 antioxidant pathway for liver protection ( 14 , 117 120 ), kidney protection ( 59 , 60 ), lung protection ( 20 ), neuroprotection ( 22 , 65 , 121 123 ), cardioprotection ( 19 , 124 , 125 ), gastrointestinal protection ( 48 , 55 , 61 , 62 , 66 , 126 128 ), anti-oxidation ( 85 , 129 134 ), anti-diabetic ( 135 137 ), anti-aging ( 138 141 ), anti-inflammation ( 67 , 69 ), anti-radiation ( 28 , 142 ), and immunomodulation ( 143 ), as illustrated in Table 1 .…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell experiments have demonstrated that NPs from herbs could regulate Nrf2 antioxidant pathway for liver protection ( 14 , 117 120 ), kidney protection ( 59 , 60 ), lung protection ( 20 ), neuroprotection ( 22 , 65 , 121 123 ), cardioprotection ( 19 , 124 , 125 ), gastrointestinal protection ( 48 , 55 , 61 , 62 , 66 , 126 128 ), anti-oxidation ( 85 , 129 134 ), anti-diabetic ( 135 137 ), anti-aging ( 138 141 ), anti-inflammation ( 67 , 69 ), anti-radiation ( 28 , 142 ), and immunomodulation ( 143 ), as illustrated in Table 1 .…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
“…Those from herbs exhibited anti-diabetic effect on palmitate-induced HepG2 cells ( 135 ), high glucose-induced ARPE-19 cells ( 136 ) or HRECs ( 146 ), and high-glucose- and high-insulin-induced 3T3-L1 adipocytes ( 137 ) by augmenting protein or mRNA expressions of p-Nrf2/Nrf2, Nrf2, HO-1, SOD2, CAT, and nuclear Nrf2 as well as nuclear translocation of p-Nrf2. NPs from herbs showed anti-aging activity against H 2 O 2 -induced chondrocytes ( 138 ), H 2 O 2 -induced ARPE-19 cells ( 139 ), ADM, ODM, ADM + H 2 O 2 , or ODM + H 2 O 2 -induced BMSCs cells ( 140 ), H 2 O 2 -induced MC3T3-E1 cells ( 141 ) through rising mRNA and/or protein expressions of Keap1, Nrf2, HO-1, and NQO1 as well as nuclear Nrf2. Polysaccharides from Dendrobium officinale ( 67 ) and Apios americana ( 69 ) produced anti-inflammation on LPS-induced RAW264.7 cells partly by adding protein and/or mRNA expressions of Keap1, Nrf2, HO-1 and NQO1.…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
“…Western blotting was performed as described [16,17]. Placental tissues were homogenized on ice and lysed in lysis buffer (Cell Signaling, cat#: 9803) by sonication.…”
Section: P R E P R I N Tmentioning
confidence: 99%